Exploring Environmental Design: Utilising Nature's Elements to Create Interactive Artistic Sculptures for Jeddah's Coastal Regions - Madani, Rafat Saleh (Journal of Posthumanism, 2025)
The objective of this study is to analyse the artistic characteristics of prominent interactive artistic sculptures, "in light of environmental design." It aims to uncover the aesthetic and philosophical dimensions of these interactive artistic sculptures, as well as to investigate the process of drawing inspiration from nature, specifically the seagull element, to showcase the aesthetics of sculptures in Jeddah. Additionally, the study aims to explore the possibility of utilising elements from nature to shape interactive and functional sculptures in Jeddah, employing three-dimensional graphic design software, namely 3D MAX. It also examines the application that combines and considers the relationship between sculptures and the environmental design of the site, while meeting the needs of the community within a visual artistic framework. The study further aims to stimulate various modes of perception and audience reception, thereby enhancing their capabilities, "in light of environmental design.